Preparation method of boron-doped porous silicon material, porous silicon material and application
By preparing boron-doped porous silicon material with uniform doping of body phase in lithium-ion batteries, the problems of poor conductivity and large volume expansion of silicon-based anode materials are solved, and the energy density and cycle stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411854114.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing silicon-based anode materials in lithium-ion batteries have limited their commercial applications due to poor conductivity, large volume expansion and unstable electrochemical performance. At the same time, the existing doping method is difficult to achieve uniform doping of Si by B, affecting the electrochemical performance of the material.
By introducing boron elements in situ while synthesizing porous silicon, using Mg powder, micron Si powder and B2O3 as raw materials, the alloying reaction, nitriding dealloyment reaction and pickling treatment were carried out to prepare boron doped porous silicon material with uniform body phase doping.
The uniform doping of Si by B is achieved, which significantly improves the conductivity and electrochemical properties of the material, alleviates the volume expansion problem during the intercalation and removal of lithium ions, and improves the energy density and cycle stability of lithium ion batteries.
Smart Images

Figure CN119315022B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a preparation method of a boron-doped porous silicon material, the porous silicon material and applications. Background Art
[0002] With the continuous expansion of electronic information products, electric vehicles (EVs) and smart grid markets, people are increasingly demanding high energy density, long cycle life and low-cost lithium-ion batteries. Currently, commercial graphite anodes have the advantages of high stability, high conductivity, low cost and abundant reserves, but their theoretical specific capacity is relatively low (372 mAh g -1 ), which is difficult to meet the current requirements for the energy density of lithium-ion batteries. In order to break through the existing limitations, researchers are working to develop a new generation of negative electrode materials with higher energy density and longer cycle life. Among them, silicon negative electrode has a very high theoretical specific capacity (4200mAhg -1 ), lower lithium extraction / insertion potential (<0.5 V vs. Li + / Li) and abundant resource reserves, it has become a potential alternative material that has attracted much attention. However, due to the poor intrinsic conductivity of silicon and the large volume expansion (>300%) during the process of lithium extraction / insertion, these problems have caused the crushing of active materials, the continuous growth of the solid electrolyte interface (SEI), and the destruction of the electronic conductive network, which in turn led to rapid battery capacity decay and reduced cycle stability, limiting the application of silicon-based negative electrode materials in the field of commercial batteries.
[0003] In order to overcome the obstacles to the commercial application of silicon anodes, researchers have proposed a variety of synthesis methods, such as etching, metal thermal reduction, and metal-assisted chemical corrosion. However, these methods are limited in terms of operational complexity, environmental friendliness, pore size control, and expensive raw materials, making them difficult to apply on a large scale. In addition, in the preparation process of B-doped Si, the high-temperature decomposition method of boron oxide can only achieve B doping of the surface or subsurface Si layer of Si, and cannot achieve B doping of Si in the bulk phase. In fact, the ratio and distribution of B atoms replacing Si atoms have a significant effect on the electrochemical properties of silicon materials. Therefore, using cheap raw materials and simple and easy methods to achieve B doping of Si and a porous silicon anode with uniform distribution of doping elements has become an urgent problem to be solved for the commercialization of silicon anodes. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the main purpose of the present invention is to provide a method for preparing a boron-doped porous silicon material, a porous silicon material and an application thereof. By in-situ introducing the boron element while synthesizing porous silicon, uniform bulk doping of Si with B is achieved. The raw materials used are cheap and easily available, the preparation process is simple and easy, and the material has the potential for industrial large-scale production.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] The first object of the present invention is to provide a method for preparing a boron-doped porous silicon material, comprising the following steps:
[0007] Step (1): Mixing Mg powder, micron Si powder and B2O3 as raw materials, and subjecting the mixed raw materials to alloying reaction under a protective atmosphere to prepare B-doped Mg2Si;
[0008] Step (2): subjecting the B-doped Mg2Si prepared in step (1) to a dealloying reaction with nitrogen to prepare a Mg3N2 / B-Si composite;
[0009] Step (3): acid-washing the Mg3N2 / B-Si composite prepared in step (2) to obtain a boron-doped porous silicon material.
[0010] Furthermore, in step (1), the particle size of the micron Si powder is 0.5 μm to 15 μm;
[0011] Furthermore, the particle size of the Mg powder is 15 μm to 300 μm.
[0012] Furthermore, in step (1), the molar ratio of the Mg powder to the micron Si powder is 2:1 to 3:1;
[0013] Furthermore, the molar ratio of Si:B between the micron Si powder and the B2O3 is 5:1 to 15:1.
[0014] Furthermore, the mixing treatment in step (1) is ball milling, the ball milling speed is 60r / min to 580r / min, the ball milling time is 1h to 24h, and the ball-to-material ratio is 1:1 to 20:1;
[0015] Furthermore, the temperature of the alloying reaction in step (1) is 500° C. to 700° C., and the reaction time is 1 h to 10 h.
[0016] Furthermore, the temperature of the dealloying reaction in step (2) is 500° C. to 1000° C., the reaction time is 1 h to 10 h, and the nitrogen gas flow rate is 1 sccm to 200 sccm.
[0017] Furthermore, the acid used in step (3) is selected from at least one of sulfuric acid, hydrochloric acid and nitric acid; the acid concentration is 0.5 mol / L to 3 mol / L, and the acid treatment time is 1 h to 24 h.
[0018] Furthermore, step (3) further comprises solid-liquid separation of the product after acid treatment, and vacuum drying the obtained solid, wherein the vacuum drying temperature is 30° C. to 150° C., and the drying time is 1 h to 48 h.
[0019] The second object of the present invention is to provide a boron-doped porous silicon material prepared by a method for preparing a boron-doped porous silicon material.
[0020] The third object of the present invention is to provide a silicon negative electrode material, comprising the following raw materials in weight percentage: 60% to 95% of the above-mentioned boron-doped porous silicon material, 1% to 20% of a conductive agent, and 1% to 20% of an adhesive.
[0021] A fourth object of the present invention is to provide a lithium-ion battery comprising the above-mentioned silicon negative electrode material.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention uses low-cost micron silicon, Mg powder and B2O3 as raw materials, adopts alloying method combined with nitriding dealloying process, and then designs and prepares boron-doped porous Si material through selective acid etching of byproducts in the reaction process. The synthesis method is simple and easy, with high yield and can be mass-produced. The prepared boron-doped porous silicon material has the dual advantages of doping and porous structure, and can realize the uniform bulk doping of B to Si, which provides a new way for B doping.
[0024] (2) Boron-doped porous silicon materials achieve P-type semiconductor properties by replacing atoms in the Si lattice with B atoms, significantly improving electrical conductivity. Its porous structure not only alleviates the volume expansion problem during lithium ion insertion and extraction, but also provides a shorter path for ion transport, thereby enhancing the overall electrochemical performance of the material.
[0025] (3) Compared with negative electrodes such as nano-silicon, using boron-doped micron-sized porous silicon materials as negative electrodes for lithium-ion batteries can improve the conductivity of silicon materials, buffer the huge volume expansion of silicon during the process of lithium insertion and extraction, and at the same time greatly increase the tap density of negative electrode materials, reduce the specific surface area of materials, reduce the surface side reactions between electrolyte and Si negative electrode, and significantly improve the first coulombic efficiency, electrochemical stability and rate performance of the negative electrode, thereby obtaining lithium-ion batteries with higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings used to describe these technical solutions. Obviously, the drawings described are only one embodiment of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without the need for creative work.
[0027] Figure 1 1 is the XRD spectrum of the materials involved in the process of preparing the boron-doped porous silicon material in Example 1; wherein 1 is the diffraction peak of the product formed by the alloying reaction, 2 is the diffraction peak of the product of the dealloying reaction, and 3 is the diffraction peak of the sample after pickling;
[0028] Figure 2 This is a scanning electron microscope image of the raw material micron silicon in Example 1;
[0029] Figure 3 This is a low-magnification scanning electron microscope photograph of the boron-doped porous silicon material prepared in Example 1;
[0030] Figure 4 This is a high-magnification scanning electron microscope photograph of the boron-doped porous silicon material prepared in Example 1;
[0031] Figure 5 B 1s XPS spectrum of the boron-doped porous silicon material prepared in Example 1;
[0032] Figure 6 The cycle stability of the active material / metal lithium battery of Example 1 and Comparative Example 1, wherein curve A represents Example 1 and curve B represents Comparative Example 1;
[0033] Figure 7 The rate performance of the active material / metal lithium battery of Example 1 and Comparative Example 1, wherein curve A represents Example 1 and curve B represents Comparative Example 1;
[0034] Figure 8 The 100-cycle performance curve of the battery assembled with the boron-doped porous silicon material prepared in Example 2 as the battery negative electrode active material;
[0035] Fig. 9 Performance curves of the battery assembled with the boron-doped porous silicon material prepared in Example 2 as the active material at different rates;
[0036] Fig.10 The 100-cycle performance curve of the battery assembled with the boron-doped porous silicon material prepared in Example 3 as the battery negative electrode active material. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The preparation concept of the boron-doped porous silicon material provided by the present invention is to use cheap and easily available Mg powder, silicon powder and B2O3 as raw materials, adopt an alloying method combined with a nitriding dealloying process, and then selectively etch the by-products in the reaction process with acid to design and prepare the boron-doped porous Si material, and apply it to the negative electrode field of lithium-ion batteries.
[0039] The present invention provides a method for preparing a boron-doped porous silicon material, comprising the following steps:
[0040] Step (1): Mixing Mg powder, micron Si powder and B2O3 as raw materials, and subjecting the mixed raw materials to alloying reaction under a protective atmosphere to prepare B-doped Mg2Si;
[0041] Step (2): subjecting the B-doped Mg2Si prepared in step (1) to a dealloying reaction with nitrogen to prepare a Mg3N2 / B-Si composite;
[0042] Step (3): The Mg3N2 / B-Si composite prepared in step (2) is acid-washed to obtain a B-doped porous silicon material.
[0043] In step (1) of the above preparation method, cheap and readily available Mg powder, micron Si powder and B2O3 are used as raw materials, which are first fully mixed and then alloyed under a protective atmosphere. During this process, Mg powder and micron Si powder generate Mg2Si alloy, and B2O3 is reduced to B by Mg and incorporated into Mg2Si grains to obtain B-doped Mg2Si product. The specific chemical reaction formula involved is: 5Mg+B2O3+Si→Mg2Si+3MgO+2B.
[0044] In step (2) of the above preparation method, the B-doped Mg2Si is subjected to a nitridation dealloying reaction in a N2 atmosphere to obtain Mg3N2 and B-doped micronized Si, i.e., a Mg3N2 / B-Si composite, the specific chemical reaction formula of which is: 3Mg2Si+2N2→2Mg3N2+3Si.
[0045] In step (3) of the above preparation method, the Mg3N2 / B-Si composite is subjected to an acid wash treatment to de-alloy the boron-doped porous silicon material, and the specific chemical reaction formula involved is: Mg3N2+6HCl→3MgCl2+2NH3.
[0046] It can be seen from the above steps (1) to (3) that the technical solution of the present application can achieve: in-situ introduction of boron element while synthesizing porous silicon to achieve uniform bulk doping of Si with B, and the raw materials used are cheap and easily available, and the preparation process is simple and easy. The preparation yield of boron-doped porous silicon in the embodiment can reach more than 78%, which has the potential for industrial large-scale production.
[0047] In boron-doped porous silicon materials, B doping helps to improve the conductivity of Si and promote the expansion of the lattice, further improving Li + The porous structure can alleviate the volume expansion of Si during the process of lithium extraction / insertion, thereby preventing electrode crushing, stabilizing the SEI film, and reducing the reversible capacity decay of the battery. Thanks to the dual effects of the porous structure and doping, the boron-doped porous silicon material in this application exhibits excellent electrochemical performance.
[0048] According to some embodiments of the present invention, the particle size of the micron Si powder is 0.5μm to 15μm, and the particle size of the Si powder used can be any value in the range of 0.5μm to 15μm, such as 0.5μm, 5μm, 7μm, 10μm, and 15μm.
[0049] According to some embodiments of the present invention, the particle size of the Mg powder is 15 μm to 300 μm, and the particle size of the Mg powder used can be any value in the range of 15 μm to 300 μm, such as 15 μm, 50 μm, 100 μm, 150 μm, 200 μm, and 300 μm.
[0050] In step (1), the molar ratio of Mg powder to Si powder is 2:1 to 3:1. The above molar ratio is conducive to the formation of Mg2Si alloy. Controlling a slight excess of Mg powder can help improve the conversion rate of Si powder. The molar ratio of Mg powder to Si powder can be any value in the range of 2:1 to 3:1, such as 2:1, 2.5:1 and 3:1.
[0051] According to some embodiments of the present application, the molar ratio of Si:B between the Si powder and the B2O3 is 5:1 to 15:1. The specific molar ratio of Si:B is any value within the range of 5:1 to 15:1, such as 5:1, 7:1, 10:1, 12:1, and 15:1. The proportion and distribution of B atoms replacing Si atoms have a significant effect on the electrochemical properties of silicon materials. Excessive doping may cause severe lattice deformation, thereby affecting the overall performance of the material. More preferably, the molar ratio of Si:B between the Si powder and the B2O3 is 10:1. In the preparation method of the present application, the Si powder and B2O3 are controlled within the above-mentioned molar ratio range, and the B-doped porous silicon material prepared in this embodiment has a higher first coulombic efficiency, electrochemical stability and rate performance.
[0052] According to some embodiments of the present application, the mixing treatment in step (1) is ball milling, the ball milling speed is 60r / min to 580r / min, and the specific ball milling speed can be any value within 60r / min to 580r / min, such as 60r / min, 100r / min, 150r / min, 200r / min, 300r / min and 580r / min; the ball milling time is 1h to 24h, and the specific ball milling time is any value within 1h to 24h, such as 1h, 5h, 10h, 12h, 20h, 24h; the ball milling material ratio is 1:1 to 20:1, and the specific ball milling material ratio is any ratio within the range of 1:1 to 20:1, such as 1:1, 5:1, 10:1, 15:1 and 20:1. The use of the above ball milling process parameters can help to achieve sufficient mixing of Mg powder, micron Si powder and B2O3.
[0053] According to some embodiments of the present application, the protective atmosphere in step (1) is Ar gas or Ar / H2 mixed gas; preferably, the protective gas is Ar gas;
[0054] According to some embodiments of the present application, the temperature of the alloying reaction in step (1) is 500°C to 700°C, the Gibbs free energy of the system is -557.23 kJ / mol to -533.54 kJ / mol, and B2O3 is added during the alloying process of Mg powder and Si powder, so that B2O3 can be reduced to B and incorporated into Mg2Si grains to obtain B-doped Mg2Si powder. The specific alloying reaction temperature can be any value from 500°C to 700°C, as long as the alloying reaction can be carried out, such as 600°C, and the specific reaction time can be any value from 1h to 10h, as long as it is conducive to the conversion of the reaction product, such as 6h.
[0055] According to some embodiments of the present application, the heating rate in step (1) is 1°C / min to 20°C / min; preferably, the heating rate is 5°C / min.
[0056] According to some embodiments of the present application, step (1) further comprises cooling the reaction product, and the cooling method is programmed temperature control or natural cooling; natural cooling is preferred.
[0057] According to some embodiments of the present application, the temperature of the nitriding dealloying reaction in step (2) is 500°C to 1000°C. During the reaction, when the temperature reaches the specified temperature, Mg in Mg2Si reacts with N2 to form Mg3N2, and Si is separated to form a Mg3N2 / Si composite material. The specific temperature of the nitriding dealloying reaction can be any value of 500°C to 1000°C that can carry out the nitriding reaction, such as 750°C. The specific reaction time can be any value of 1h to 10h that can facilitate the complete nitriding reaction, such as 6h. The nitrogen gas flow rate is any value of 1sccm to 200sccm, such as 40sccm.
[0058] According to some embodiments of the present application, step (2) further comprises cooling the reaction product, and the cooling method is programmed temperature control or natural cooling; natural cooling is preferred.
[0059] According to some embodiments of the present application, the acid used in step (3) is selected from at least one of sulfuric acid, hydrochloric acid and nitric acid; the acid concentration is any value within the range of 0.5 mol / L to 3 mol / L, for example, 1 mol / L; and the acid treatment time is any value within the range of 1 h to 24 h, for example, 12 h.
[0060] According to some embodiments of the present application, the dealloying reaction in step (3) is carried out under stirring, and the stirring speed is any value in the range of 50 r / min to 1000 r / min, and the stirring is, for example, magnetic stirring.
[0061] According to some embodiments of the present application, step (3) further comprises solid-liquid separation of the acid-treated product and vacuum drying of the obtained solid. The solid-liquid separation measures adopted include but are not limited to suction filtration, centrifugation, etc. In order to reduce the residual impurities, washing can also be performed after the solid-liquid separation operation, for example, washing with deionized water and anhydrous ethanol. The specific vacuum drying temperature is any value in the range of 30°C to 150°C, for example, 60°C, 100°C and 150°C, and the specific drying time is any value in the range of 1h to 48h, for example, 1h, 12h, 24h and 48h.
[0062] Another embodiment of the present invention provides a boron-doped porous silicon material prepared by the above-mentioned preparation method. The boron-doped porous silicon material obtained by the above-mentioned preparation method realizes the uniform doping of B to the Si bulk phase, which can greatly improve the conductivity of the silicon material. The product powder has a micron-sized appearance, has a micro / nano hierarchical structure, and presents a three-dimensional continuous channel structure rich in a large number of voids inside. The obtained micron porous silicon also has a micro / nano hierarchical porous structure with macroscopic and microscopic multi-scale pore distribution. It not only effectively alleviates the volume expansion problem of silicon during the charging and discharging process, but also provides a three-dimensional continuous channel for lithium ion / electron transmission. The three work together to give micron-sized porous silicon the characteristics of high conductivity, high tap density, low specific surface area, high first coulomb efficiency, high specific capacity and excellent cycle stability.
[0063] Another embodiment of the present invention provides a silicon negative electrode material, comprising the following raw materials in weight percentage: 60% to 95% of the above-mentioned boron-doped porous silicon material, 1% to 20% of a conductive agent, and 1% to 20% of a binder.
[0064] The silicon negative electrode material can be made by the following process: the boron-doped porous silicon material, the conductive agent and the binder are mixed in proportion to form a slurry, and then coated on the Cu foil, and then dried to serve as the silicon negative electrode.
[0065] According to some embodiments of the present application, the conductive agent is one or more of acetylene black, Ketjen black, carbon nanotubes, and graphene;
[0066] According to some embodiments of the present application, the binder is one or more of sodium alginate, carboxymethyl cellulose, and polyvinylidene fluoride.
[0067] Another embodiment of the present invention provides a lithium-ion battery, comprising the silicon negative electrode material. The lithium-ion battery provided by the present application can have a higher first coulombic efficiency, electrochemical stability and rate performance of the negative electrode.
[0068] The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0069] Example 1
[0070] (1) Commercial Si powder (7 μm), Mg powder (150 μm) and B2O3 were weighed according to Mg:Si = 2:1, Si:B = 10:1 (molar ratio), and placed in a planetary ball mill for 12 h at 300 rpm, where the ball-to-material ratio was 10:1. The ball-milled mixture was poured into a corundum boat, placed in a tube furnace, and heated to 600°C at a rate of 5°C / min under Ar atmosphere, kept at this temperature for 6 h, and then naturally cooled to room temperature 25°C under Ar gas protection atmosphere and taken out. The obtained blue-blue sample powder is the B-doped Mg2Si material.
[0071] (2) The powder obtained in step (1) was spread on a porcelain boat, placed in a tube furnace, and heated to 750 °C at a rate of 5 °C / min under a N2 atmosphere with a gas flow rate of 40 sccm. The mixture was kept at this temperature for 6 h and naturally cooled to room temperature under a N2 atmosphere. Finally, a brown-yellow powder was obtained, which was the B-doped Mg3N2 / Si composite material.
[0072] (3) The powder obtained in step (2) was magnetically stirred in a 1 mol / L dilute hydrochloric acid solution at 500 rpm for 12 h to remove by-products MgO, Mg3N2 and unreacted Mg2Si, followed by filtration and cleaning, washing with deionized water and anhydrous ethanol alternately for 3 times, and vacuum drying at 60 °C for 8 h to obtain a boron-doped porous silicon material.
[0073] Comparative Example 1
[0074] (1) Commercial Si powder (7 μm) and Mg powder (150 μm) were weighed at a ratio of Mg:Si = 2:1 and placed in a planetary ball mill for 12 h at a speed of 300 rpm, with a ball-to-material ratio of 10:1. The ball-milled mixture was poured into a corundum boat, placed in a tube furnace, and heated to 600 °C at a rate of 5 °C / min under an Ar atmosphere for 6 h. Then, it was naturally cooled to room temperature of 25 °C under an Ar gas protective atmosphere and taken out. The obtained blue-green sample powder was the Mg2Si material.
[0075] (2) The powder obtained in step (1) was spread on a porcelain boat, placed in a tube furnace, and heated to 750 °C at a rate of 5 °C / min under a N2 atmosphere with a gas flow rate of 40 sccm. The mixture was kept at this temperature for 6 h and naturally cooled to room temperature under a N2 atmosphere to finally obtain a brown-yellow powder, which is the Mg3N2 / Si composite material.
[0076] (3) The powder obtained in step (2) was magnetically stirred in a 1 mol / L dilute hydrochloric acid solution at 500 rpm for 12 h to remove by-products MgO, Mg3N2 and unreacted Mg2Si, followed by filtration and cleaning, washing with deionized water and anhydrous ethanol alternately for 3 times, and vacuum drying at 60 °C for 8 h to obtain a porous silicon material.
[0077] The boron-doped porous silicon material and porous silicon material (as active material) obtained in Example 1 and Comparative Example 1 were mixed and ground evenly with a conductive agent (SP) and a binder (sodium alginate) in a mass ratio of 8:1:1, coated on a copper foil, and dried at 60°C for 12 h. A polypropylene film (Celgard 2400) was used as a diaphragm, a metal lithium foil was used as a counter electrode, and a mixed solution of 1 M lithium hexafluorophosphate (LiPF6) in ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (1:1:1, v:v:v) was added with 10% fluoroethylene carbonate (FEC) as an electrolyte, and the amount of electrolyte was 2 to 3 drops, and a complete CR2032 button cell was assembled. The whole process was completed in a glove box filled with Ar gas and with a water and oxygen content of less than 0.01 ppm, and the assembled battery was left to stand for more than 12 h. The electrode was tested for cycle performance using a constant current charge and discharge technique (GCD). The voltage window is 0.01-1.5 V and the test current density is 0.2 A g -1 ~4 A g -1 .
[0078] The materials and the prepared materials in the above process of Example 1 were analyzed by X-ray diffraction technology (XRD), and the results are shown in Figure 1 ,from Figure 1 It can be seen that the diffraction peaks of the product (B-doped Mg2Si) formed by the alloying reaction are consistent with the Mg2Si phase (JCPDS: 35-0773) and the MgO phase (JCPDS: 77-2179). Among these two products, Mg2Si is the main component and MgO is a by-product. When the B-doped Mg2Si is further alloyed in a N2 atmosphere, the diffraction peaks of the Mg3N2 phase (JCPDS: 73-1070), Si phase (JCPDS: 77-2107) and MgO phase can be observed, which indicates that Mg2Si completely reacts with it in a N2 atmosphere to form a Mg3N2 / Si composite material. Finally, the three strong peaks of the sample at 28.5°, 47.4° and 56.2° after pickling correspond to the three strong peaks of Si, and there is basically no impurity phase. Figure 2 This is a scanning electron microscope image of the raw material micron silicon of Example 1. Figure 3 This is a low-magnification scanning electron microscope photograph of the boron-doped porous silicon material prepared in Example 1; Figure 4 This is a high-magnification scanning electron microscope photograph of the boron-doped porous silicon material prepared in Example 1; Figure 2 to Figure 4 It can be seen that the original micron silicon particle size is about 7 μm, with a rough and dense surface. The microstructure of boron-doped porous silicon exhibits a complex porous morphology with macroscopic and microscopic multi-scale pores. This structure is composed of interconnected large pores and small pores, forming a multi-level pore network. Figure 5 This is the B1s XPS spectrum of the boron-doped porous silicon material prepared in Example 1. The two peaks in the figure correspond to B-Si and BB bonds, respectively, which indicates that B has been successfully doped into Si.
[0079] The electrochemical performance of the battery assembled with the boron-doped porous silicon material of Example 1 and the porous silicon material of Comparative Example 1 was tested. -1 The constant current cyclic charge and discharge test was carried out at a current density of , and the cycle number-specific capacity curve obtained is as follows Figure 6 As shown in the figure, curves A and B are respectively the boron-doped porous silicon prepared in Example 1 of the present invention and the porous silicon in Comparative Example 1 as an active material at 0.2 A g -1 After 3 cycles of activation at a current density of 0.5 A g -1 The cycling stability of the product after 100 cycles at a current density of Figure 6 It can be seen that the initial Coulomb efficiency of the boron-doped porous silicon of Example 1 is as high as 83.68%, while the initial Coulomb efficiency of the porous silicon of Comparative Example 1 is 71.63%. The reason for this difference is that a small amount of B doping can greatly improve the conductivity. In addition, after 100 cycles, the specific capacity of the boron-doped porous silicon material can still reach 1914.4 mAh g -1 , while the porous silicon material is only 180.2 mAh g -1 , indicating that the doped porous silicon material shows excellent cycle stability. This stability is achieved thanks to the multi-level porous structure design of the material, which effectively alleviates the stress caused by the volume expansion of silicon during the charge and discharge process, thereby maintaining the integrity of the electrode structure and the long-term stability of the electrochemical performance. In addition, the assembled battery was tested for rate performance, and the results are as follows Figure 7 As shown in the figure, curves A and B are respectively the boron-doped porous silicon prepared in Example 1 of the present invention and the porous silicon in Comparative Example 1 as an active material at 0.2 A g -1 ~4 A g -1 The rate performance tested under current density is determined by Figure 7 It can be seen that boron-doped porous silicon has a rate performance far superior to that of porous silicon. -1 , 0.5A g -1 , 1A g -1 , 2A g -1 , 4A g -1 The specific capacities at current densities of 3129.2 mAh g-1 、2873.3 mAh g -1 、2552.5 mAh g -1 、2231.3 mAh g -1 、1609.4 mAh g -1 When the current density returns to 0.5 A g -1 When the battery is fully charged, it still shows a high capacity of 2556.5 mAh g -1 The specific capacity of boron-doped porous silicon material shows excellent rate performance and capacity recovery ability. In summary, boron-doped porous silicon material exhibits excellent electrochemical performance and has good application prospects.
[0080] Example 2
[0081] In this embodiment, a strategy of doping with a smaller amount of B is adopted to design and prepare a boron-doped porous silicon material.
[0082] (1) Commercial Si powder (7 μm), Mg powder (150 μm) and B2O3 were weighed according to Mg:Si = 2:1, Si:B = 15:1 (molar ratio) and placed in a planetary ball mill for 12 h at 300 rpm, where the ball-to-material ratio was 10:1. The ball-milled mixture was evenly spread on a corundum porcelain boat, placed in a tube furnace, and heated to 600 °C at a heating rate of 5 °C / min in an Ar atmosphere. The heat treatment process was completed for 6 h, and then naturally cooled to room temperature 25 °C in an Ar gas protective atmosphere and taken out to obtain B-doped Mg2Si material.
[0083] (2) The powder obtained in step (1) was evenly spread on a porcelain boat, placed in a tube furnace, and heated to 750 °C at a heating rate of 5 °C / min in a N2 atmosphere with a gas flow rate controlled at 40 sccm. The mixture was kept warm for 6 h and naturally cooled to room temperature in a N2 atmosphere to obtain a B-doped Mg3N2 / Si composite material.
[0084] (3) The powder obtained in step (2) was magnetically stirred in a 1 mol / L dilute hydrochloric acid solution at 500 rpm for 12 h to remove by-products MgO, Mg3N2 and unreacted Mg2Si, followed by filtration and washing, alternating washing with deionized water and anhydrous ethanol for 3 times, and vacuum drying at 60 °C for 8 h to obtain a boron-doped porous silicon material.
[0085] (4) The boron-doped porous silicon material (as active material) obtained in (3) was mixed with a conductive agent (SP) and a binder (sodium alginate) in a mass ratio of 8:1:1, ground evenly, coated on a copper foil, and dried at 60 °C for 12 h. A polypropylene film (Celgard 2400) was used as a separator, a metal lithium foil was used as a counter electrode, and a 1 M lithium hexafluorophosphate (LiPF6) mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (1:1:1, v:v:v) was added with 10% fluoroethylene carbonate (FEC) as an electrolyte to assemble a complete CR2032 button cell. The whole process was completed in a glove box filled with Ar gas and with a water and oxygen content of less than 0.01 ppm. The assembled battery was left to stand for more than 12 h. The cycling performance of the electrode was tested using a constant current charge and discharge technique (GCD). The voltage window is 0.01-1.5 V and the test current density is 0.2 A g -1 ~4 A g -1 .
[0086] The electrochemical performance of the battery assembled with boron-doped porous silicon material was tested. -1 After 3 cycles of activation at 0.5 A g -1 The current density was cycled 100 times. The results are as follows Figure 8 As shown, at 0.2 A g -1 It can show 3152.7 mAh g -1 High specific capacity. At 0.5A g -1 The initial specific capacity at the current density is 2177.1 mAh g -1 After 100 cycles, the capacity can still reach 1518.7 mAh g -1 , showing good cycle stability. In addition, the assembled battery was tested for rate performance, and the results are as follows Fig. 9 As shown, at 0.2 A g -1 , 0.5 A g -1 , 1 A g -1 , 2 A g -1 、4Ag -1 The charge and discharge tests were carried out at current densities of 3458.8 mAh g -1 、2603.3 mAh g -1 、2208.3 mAh g -1 、1821.9 mAh g -1 、1032.5 mAh g -1 When the current density returns to 0.2 A g -1When the battery is fully charged, it still shows a high capacity of 2436.5 mAh g -1 The specific capacity of boron-doped porous silicon material shows excellent electrochemical performance and good application prospects.
[0087] Example 3
[0088] In this embodiment, a larger amount of B doping strategy is adopted to design and prepare a boron-doped porous silicon material.
[0089] (1) Commercial Si powder (7 μm), Mg powder (150 μm) and B2O3 were weighed according to Mg:Si = 2:1, Si:B = 5:1 (molar ratio), and placed in a planetary ball mill for 12 h at 300 rpm, where the ball-to-material ratio was 10:1. The ball-milled mixture was poured into a corundum boat, placed in a tube furnace, and heated to 600 °C at a rate of 5 °C / min under Ar atmosphere, kept at this temperature for 6 h, and then naturally cooled to room temperature 25 °C under Ar gas protection atmosphere and taken out. The obtained blue-blue sample powder is the B-doped Mg2Si material.
[0090] (2) The powder obtained in step (1) was spread on a porcelain boat, placed in a tube furnace, and heated to 750 °C at a rate of 5 °C / min under a N2 atmosphere with a gas flow rate of 40 sccm. The mixture was kept at this temperature for 6 h and naturally cooled to room temperature under a N2 atmosphere. Finally, a brown-yellow powder was obtained, which was the B-doped Mg3N2 / Si composite material.
[0091] (3) The powder obtained in step (2) was magnetically stirred in a 1 mol / L dilute hydrochloric acid solution at 500 rpm for 12 h to remove by-products MgO, Mg3N2 and unreacted Mg2Si, followed by filtration and cleaning, washing with deionized water and anhydrous ethanol alternately for 3 times, and vacuum drying at 60 °C for 8 h to obtain a boron-doped porous silicon material.
[0092] (4) The boron-doped porous silicon material (as active material) obtained in (3) was mixed with a conductive agent (SP) and a binder (sodium alginate) in a mass ratio of 8:1:1, ground evenly, coated on a copper foil, and dried at 60 °C for 12 h. A polypropylene film (Celgard 2400) was used as a separator, a metal lithium foil was used as a counter electrode, and a 1 M lithium hexafluorophosphate (LiPF6) mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (1:1:1, v:v:v) was added with 10% fluoroethylene carbonate (FEC) as an electrolyte, and the amount of electrolyte was 2 to 3 drops to assemble a complete CR2032 button cell. The whole process was completed in a glove box filled with Ar gas and with a water and oxygen content of less than 0.01 ppm. The assembled battery was left to stand for more than 12 h. The cycling performance of the electrode was tested using a constant current charge and discharge technique (GCD). The voltage window is 0.01-1.5 V and the test current density is 0.2 A g -1 ~4 A g -1 .
[0093] The electrochemical performance of the battery assembled with boron-doped porous silicon material was tested. -1 After 3 cycles of activation at 0.5 A g -1 The current density was cycled 100 times. The results are as follows Fig.10 As shown, at 0.2 A g -1 It can show 1457.4 mAh g -1 High specific capacity at 0.5 A g -1 The initial specific capacity at this current density is 1135.3 mAh g -1 , showing good cycle performance.
[0094] In summary, boron-doped porous silicon materials have excellent electrochemical properties, with high specific capacity, good cycle stability and excellent rate performance. These characteristics provide a solid foundation and broad development prospects for their application in the field of high-performance lithium-ion battery negative electrode materials.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application and not to limit it. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present application can still be modified or some technical features can be replaced by equivalents, which should all be included in the scope of the technical solution requested for protection in this application.
Claims
1. A method for preparing a boron-doped porous silicon material, characterized in that: The following steps are involved: Step (1): Mixing Mg powder, micron Si powder and B2O3 as raw materials, and subjecting the mixed raw materials to alloying reaction under a protective atmosphere to prepare B-doped Mg2Si; Step (2): subjecting the B-doped Mg2Si prepared in step (1) to a dealloying reaction with nitrogen to prepare a Mg3N2 / B-Si composite; Step (3): acid-washing the Mg3N2 / B-Si composite prepared in step (2) to obtain a boron-doped porous silicon material; In step (1), the molar ratio of the Mg powder to the micron Si powder is 2.5:1 to 3:1; the molar ratio of the micron Si powder to the B2O3 is 5:1 to 15:1 according to Si:B; The temperature of the alloying reaction in step (1) is 500°C to 700°C, and the reaction time is 1h to 10h; The temperature of the dealloying reaction in step (2) is 500°C to 1000°C, and the reaction time is 1h to 10h; The boron-doped porous silicon material has a powder shape of micrometer size and a three-dimensional continuous channel structure rich in pores. The boron-doped porous silicon has a micro / nano graded porous structure with macroscopic and microscopic multi-scale pore distribution.
2. The method for preparing a boron-doped porous silicon material according to claim 1, characterized in that: In step (1), the particle size of the micron Si powder is 0.5 μm to 15 μm; The particle size of the Mg powder is 15 μm to 300 μm.
3. The method for preparing a boron-doped porous silicon material according to claim 1, characterized in that: The mixing treatment in step (1) is ball milling, the ball milling speed is 60r / min to 580r / min, the ball milling time is 1h to 24h, and the ball-to-material ratio is 1:1 to 20:
1.
4. The method for preparing a boron-doped porous silicon material according to claim 1, characterized in that: In step (2), the nitrogen gas is introduced at a flow rate of 1 sccm to 200 sccm.
5. The method for preparing a boron-doped porous silicon material according to claim 1, characterized in that: The acid used in step (3) is selected from at least one of sulfuric acid, hydrochloric acid and nitric acid; the acid concentration is 0.5 mol / L to 3 mol / L, and the acid treatment time is 1 h to 24 h.
6. The method for preparing a boron-doped porous silicon material according to claim 1, characterized in that: Step (3) further comprises solid-liquid separation of the acid-treated product and vacuum drying of the obtained solid, wherein the vacuum drying temperature is 30° C. to 150° C. and the drying time is 1 h to 48 h.
7. The boron-doped porous silicon material prepared by the preparation method according to any one of claims 1 to 6.
8. A silicon negative electrode material, characterized in that: The invention comprises the following raw materials in weight percentage: 60% to 95% of the boron-doped porous silicon material as claimed in claim 7, 1% to 20% of a conductive agent, and 1% to 20% of an adhesive.
9. A lithium ion battery, characterized in that: Comprising the silicon negative electrode material as described in claim 8.
Citation Information
Patent Citations
Sheet-shaped boron-doped porous silicon electrode material and preparation method thereof
CN108390053A
Externally-coated porous silicon material, preparation method and application thereof
CN114094087A